THE GENRES OF MLK’S ”I HAVE A DREAM” - Ahmad Idris Asmaradhani (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2009)
ABSTRACTIn general, official speeches, either political or general speeches,in Indonesia linguistically use more direct-language. That is, the meanings or thoughts in the speeches can be understood simply through—to use Brown et al’s terms—the “process of fairly basic linguistic ability”(see: Brown et al., 1994: 13). This kind of speech is in one way or theother quite acceptable when the speech is meant to deliver somesimple information. In other words, this way of conveying a thesis is suitable when it is simply to inform. When the purpose of the speech ismeant to win the assent of the audience, however, in one way or theother it should be presented differently. That is, although a speech isin a formal and official setting, it should—by the justification of the listeners as the community of minds— be rhetorically acceptable to most(if not all) audience. To meet that purpose, the speaker should presenthis idea persuasively, argumentatively, intellectually, and cooperatively—that is, in terms of linguistics, rhetorically.